2011
DOI: 10.1128/jb.05492-11
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium smegmatis RoxY Is a Repressor ofoxySand Contributes to Resistance to Oxidative Stress and Bactericidal Ubiquitin-Derived Peptides

Abstract: The mycobactericidal properties of macrophages include the generation of reactive oxygen intermediates and the delivery of bacteria to a hydrolytic lysosome enriched in bactericidal ubiquitin-derived peptides (Ubpeptides). To better understand the interactions of ubiquitin-derived peptides with mycobacteria and identify putative mycobacterial intrinsic resistance mechanisms, we screened for transposon mutants with increased susceptibility to the bactericidal Ub-peptide Ub2. We isolated 27 Mycobacterium smegmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Overexpression of OxyS in M. smegmatis reduced transcription of the AhpCD genes, which encode a peroxide detoxification system. Thus, RoxY, OxyS, and AhpD play a role in the mycobacterial oxidative stress response, and are important for resistance to host antimicrobial peptides [204].…”
Section: Other Bacterial Survival Strategies Bacterial Inhibition Of mentioning
confidence: 99%
“…Overexpression of OxyS in M. smegmatis reduced transcription of the AhpCD genes, which encode a peroxide detoxification system. Thus, RoxY, OxyS, and AhpD play a role in the mycobacterial oxidative stress response, and are important for resistance to host antimicrobial peptides [204].…”
Section: Other Bacterial Survival Strategies Bacterial Inhibition Of mentioning
confidence: 99%
“…Alkyl hydroperoxide reductase C (AhpC) is a member of the peroxiredoxin family that catalyzes reduction of organic peroxides and H 2 O 2 into corresponding alcohols and water respectively (Wood et al ., ). The ahpC gene and its downstream gene ahpD encoding peroxiredoxin reductase form an operon in Mycobacterium smegmatis (Daugherty et al ., ). Since AhpC is capable of detoxifying peroxide species and peroxynitrite (ONOO − ) through its enzymatic activity catalyzing the reduction of the peroxide linkage (OO), it has been suggested that this enzyme plays an important role in protection of mycobacterial cells from harmful effects of ONOO − (Master et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…It was reported that AhpC can be also reduced by thioredoxin C (TrxC) and NADPH-dependent thioredoxin reductase [10] . The ahpC gene forms an operon with its downstream gene, ahpD [11] . Genes encoding the OxyR homologs, which are LysR family regulators and involved in peroxide stress response, are divergently located upstream of the ahpCD operons in most mycobacteria [12] .…”
Section: Introductionmentioning
confidence: 99%